Numerical analysis and control technology of gas accumulation in a large-scale specially-shaped tunnel passing through coal bearing strata - Ma, Shu; Mi, Wansheng; Fan, Shixing; Qiu, Rui; Niu, Gongqueshang (Frontiers in Earth Science, 2023)
To solve the construction ventilation problem of super long (length greater than 10000m) tunnel passing through discrete lenticular gas bag tunnel under complex working conditions in carbonaceous shale stratum, relying on the construction of Banzhulin tunnel of the new Xuyong-Bijie Railway (Sichuan-Yunnan). Using the finite element analysis software, the flow field distribution of the tunnel return air flow in the case of simultaneous excavation of multiple working faces is simulated, and the formation position and influence range of the vortex area which is easy to form gas accumulation are analyzed. On this basis, the technical team developed the PLC uninterruptible self starting ventilation power supply control program. By comparing the changes in the time required for ventilation power supply failure before and after the adoption of this technology, and the comparison of the gas concentration in the return air flow within a relatively short time of the failure, it is proved that this technology reduces the fault response time to 15.74% of the original time, and can well avoid gas accumulation within the failure time, It provides some reference for similar engineering construction.